The course of pregnancy and delivery and the use of maternal healthcare services after standard IVF in Northern Finland 1990-1995 - Koivurova, Sari; Hartikainen, Anna-Liisa; Karinen, Liisa; Gissler, Mika; Hemminki, Elina; Martikainen, Hannu; Tuomivaara, Leena; Järvelin, Marjo-Riitta (Human Reproduction, 2002)
BACKGROUND: The objective of this study was to evaluate the course of pregnancy and delivery and the use of maternal healthcare after IVF. METHODS: This population-based cohort study included all women who had undergone IVF treatment in Northern Finland leading to delivery in 1990–1995 ( n = 225) and control pregnancies derived from the Finnish Medical Birth Register ( n = 671) matched for sex of the child, year of birth, area, maternal age, parity, social class and fetal plurality. The analyses were stratified by plurality. Outcome measures were pregnancy complications, mode of delivery, gestational length and the level of use of antenatal care. RESULTS: The results showed an increased risk for vaginal bleeding throughout pregnancy [relative risk (RR) 4.1, 95% confidence interval (CI) 2.5–6.7 for singletons; RR 6.9, 95% CI 2.5–19.2 for twins], threatened preterm birth (RR 1.8, 95% CI 1.1–2.9, singletons) and intrahepatic cholestasis of pregnancy (RR 3.8, 95% CI 1.0–15.0, singletons) in IVF pregnancies, as well as an increase in the use of specialized antenatal care. CONCLUSIONS: IVF pregnancies following standard, fresh ova IVF treatments are at greater risk of obstetric problems than spontaneously conceived pregnancies, and hence IVF mothers use more specialized antenatal care than others. The pregnancy complications after IVF are likely to be due to maternal characteristics regarding infertility and to a high incidence of multiple pregnancies.